A new species of Seira Lubbock (Collembola: Entomobryidae) from Brazil with sexually dimorphic legs - Bellini, Bruno Cavalcante; Pais, Alexandra Peregrino; Zeppelini, Douglas (Zootaxa, 2009)
A new species of Seira Lubbock, S. bicolorcornuta sp. nov., from Alto do Moura, Pernambuco State, Brazil, is described and illustrated. The males of this species have conspicuous modifications on the first pair of legs. This condition and other morphological features indicate a clear relationship between S. bicolorcornuta sp. nov. and S. raptora Zeppelini & Bellini. The distribution and chaetotaxic patterns of both species are discussed.